Digital transformation in servitization: analysis of technologies and dominant themes - Giuliani Facco; Paulo Augusto Cauchick Miguel; Thayla Tavares de Sousa Zommer (Gestão & Produção)
Abstract Digital servitization is a trend in which companies offer additional services to products. Digital technologies play a crucial role in this process, providing insights and improving the customer experience. In this context, this article seeks to analyze the literature on digital servitization, identifying the dominant themes and technologies used in this attempt. The work was conducted through a systematic literature review, which resulted in 130 articles analyzed, classified and coded, resulting in 9 main themes and 16 topics on digital technologies. Digital Technologies open up new perspectives and impose significant challenges on companies, compelling them to develop completely innovative business models, abandoning traditional product-centric approaches in favor of service-oriented strategies (based on digitalization). This article contributes to this line of research in different ways. First, it proposes a theoretical map, where the research field is segmented into three levels: domain, themes and topics, bringing digital servitization as a general plan, which helps in understanding company transitions caused by technologies, bringing theoretical and managerial contributions. Furthermore, the results describe a rapidly growing core of contributions that revolve around this research domain, where gaps were also identified, mainly regarding studies on digital servitization ecosystems and their interrelations with other relevant themes that are also part of of this transformation.